Lifetime cancer risks from hazardous air pollutants in US public school districts. Issue 9 (14th June 2019) - Grineski, Sara Elizabeth; Collins, Timothy
Abstract : Background: Children are sensitive to the health impacts of environmental contaminants, but research assessing outdoor environmental exposures for children and schools is underdeveloped. There are no national-level studies examining geographical and social disparities in air pollution exposure for children in school districts. Focusing on school districts is important because they are meaningful decision-making entities for schools. Methods: Using data from the National Air Toxics Assessment, we spatially reallocated lifetime cancer risk (LCR) from hazardous air pollutants (HAPs) within US school district boundaries, and paired those estimates with school district level sociodemographic measures obtained through the Integrated Public Use Microdata Series National Historic Geographic Information System. We employed local Moran's I to identify district-level hotpots and generalised estimating equations (GEEs) to quantify risk disparities. Results: We identified hotspots of elevated LCR from all sources of HAPs (called 'total'). A regional hotspot extends throughout the southeastern USA and smaller regional hotspots are present in southern Arizona, southern California and in California's central valley. School districts with higher proportions of children, children with disabilities, foreign-born children, black children and multiracial/other race children, and lower proportions of Native American children, had greater total LCR (p<0.001). The effect of poverty on total LCR (p<0.001) was nonlinear; the lowest and highest poverty districts had lower total LCR. Conclusions: Geographical and social disparities in LCR across US school districts may be affecting children's health and future potential. This new knowledge can inform policy changes, as school districts can advocate for the environmental health of children.